DO LEADERSHIP AND COMMUNICATION STYLES PLAY AN IMPORTANT ROLE IN EMPLOYEE PERFORMANCE? - Erlita Octaria; Riza Bahtiar Sulistyan; Anisatul Fauziah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
Writing this study aims to determine the influence of leadership style and communication on employee performance. The background of this research is that employee performance is very important in organizations and institutions, where performance is the result of work that can be achieved either individually or in groups within an organization in accordance with their respective responsibilities. One of the successes or failures of an organization is the leadership that runs within the organization. A successful leader is a leader who is able to create good communication and encourage his subordinates by creating growth and development of employee performance. The population and sample in this study were employees of the Lumajang District Social Service as many as 40 respondents. The sampling technique is probability sampling with simple random sampling technique and the collection method is using a questionnaire. The data analysis method used multiple linear regression analysis. The results of this study indicate that leadership style has a significant effect on employee performance, while communication has no significant effect on employee performance at the Lumajang Regency Social Service.